Chorea in a patient with cryopyrin-associated periodic syndrome - Schwarzbach, Christopher Jan; Schmitt, Wilhelm; Szabo, Kristina; Bäzner, Hansjörg; Hennerici, Michael G.; Blahak, Christian (Neurology, 2016)
Objective: To describe a patient with cryopyrin-associated periodic syndrome (CAPS) with an uncommon neurologic phenotype and a rare underlying genetic mutation. Results: Our patient had CAPS with a rare NLPR3 missense mutation (p.Tyr859Cys) in exon 6 with chorea as the major symptom. Clinical symptoms were associated with persistent inflammatory changes of the CSF and serum and included elevated anticardiolipin immunoglobulin G; MRI showed prolonged gadolinium enhancement of 2 chronic inflammatory lesions. Conventional immunosuppressive treatment with prednisolone and hydroxychloroquine was insufficient. Neurologic symptoms, laboratory/chemical measures, and MRI abnormalities almost completely normalized following interleukin (IL)-1β blockade with anakinra. Conclusions: This case is unique for its uncommon neurologic phenotype, the rare underlying genetic mutation, and the long course of the disease as well as almost complete recovery following appropriate therapy. In addition, the chronic inflammatory white matter lesions observed on brain MRI and the responsiveness to IL-1β blockade with anakinra are unusual.